The Effect of Village Community Economic Empowerment on Poverty Reduction in Rantau Bayur District of Banyuasin Regency - Salim, Agus (Utan Kayu Publishing, 2022)
Community economic empowerment is an important thing to improve the village economy and also the community so that people who are still said to be poor can be empowered. One program that is expected to be able to move the wheels of the economy, especially the rural economy, is the BUMDes which has been formed in each village, in Rantau Bayur District, Banyuasin Regency. BUMDes was created by the government in an effort to alleviate poverty and improve village economic efforts based on the needs and potentials that exist in the village. The purpose of this study was to determine how much influence the economic empowerment of rural communities has on poverty alleviation in Rantau Bayur District, Banyuasin Regency. This research is a quantitative approach, using simple random aside with the data collection methods that the authors use are questionnaires (questionnaires) and documentation. The results of instrument testing were conducted on 50 respondents with a total of 33 statement items, it was declared valid and could be used to collect data on the research sample. The population in this study was the entire community of Tebing Abang Village, Rantau Bayur District, Banyuasin Regency, while the research sample amounted to 96 respondents from the Tebing Abang Village community. While the data analysis technique used is the Pearson product-moment correlation analysis technique and the simple linear regression analysis technique using SPSS 23.0. The results of this study indicate that the correlation between community economic empowerment and poverty alleviation is 0.855. Based on the level of reliability, Cronbach alpha is in the